Rare earth minerals : chemistry, origin and ore deposits - Jones, Adrian P; Wall, Frances; Williams, C. Terry; Mineralogical Society (Great Britain) (London : Chapman & Hall, 1996)
"This is the first book to give an overview of this geologically and industrially important group of minerals. The book concentrates on the minerals themselves rather than whole rock geochemistry, and presents a wide range of information - crystal structures, petrographic descriptions, analytical data and numerous illustrations from outcrop photos to SEM pictures and crystallographic models." "The book starts with an expert review of the geochemical behaviour of Rare Earth elements, and an up-to-date review of Rare Earth minerals based on crystal structures and a new classification of perovskite. There is a chapter on pressure and temperature stabilities of some igneous RE minerals based on experimental work, and a chapter on RE minerals in China (with geological maps) much of which is entirely new. Subsequent chapters have been selected to illustrate the wide variety of different geological settings where RE minerals occur, from alkaline igneous rocks through hydrothermal ores and metamorphic skarns to very recent work on RE-mineralized carbonatites and laterites and bauxites." "This book will be essential reading for research workers in mineralogy, geology, materials science and economic geology. It will also be a valuable source of information for third-year earth science undergraduates."--Jacket
-- The rare earth elements: introduction and review / P. Henderson -- Crystal chemical aspects of rare earth minerals / R. Miyawaki and I. Nakai -- Perovskites: a revised classification scheme for an important rare earth element host in alkaline rocks / R.H. Mitchell -- Rare earth elements in carbonate-rich melts from mantle to crust / P.J. Wyllie, A.P. Jones and J. Deng -- Formation of rare earth minerals in hydrothermal systems / R. Giere -- Rare earth minerals from the syenite pegmatites in the Oslo region, Norway / A.O. Larsen -- Rare earth element mineralization in peralkaline systems: the T-Zone REE-Y-Be deposit, Thor Lake, Northwest Territories, Canada / R.P. Taylor and P.J. Pollard -- Rare earth minerals in carbonatites: a discussion centred on the Kangankunde Carbonatite, Malawi / F. Wall and A.N. Mariano -- REE distribution and REE carriers in laterites formed on the alkaline complexes of Araxa and Catalao (Brazil) / G. Morteani and C. Preinfalk -- Authigenic rare earth minerals in karst-bauxites and karstic nickel deposits / Z.J. Maksimovic and Gy. Panto -- Rare earth deposits in China / C. Wu, Z. Yuan and G. Bai -- Yttrium and rare earth element minerals of the Kola Peninsula, Russia / A.P. Belolipetskii and A.V. Voloshin -- Analysis of rare earth minerals / C.T. Williams -- Glossary of rare earth minerals
"Selected papers and additional contributions based on the conference Rare earth minerals ... at the Natural History Museum in April 1993"--Preface
Includes bibliographical references and index
Keywords: Rare earth metals; Minerals